A comparison of general versus regional anesthesia in patients over 100 years old: A retrospective cohort study (Annals of Medical Research, 2021)
Aim: As the life expectancy maintains to rise, the number of centenarians applied for surgery is increasing. Functional and anatomical changes in elderly patients may cause postoperative morbidity and mortality. The aim of this retrospective cohort study is to analyze and compare general and regional anesthesia in centenarians underwent different surgeries.Material and Methods: Patients aged over 100 years (American Society of Anesthesiology scores of II–IV) were included in our study. The centenarians were divided into two study groups: general anesthesia (Group GA, n=20) and regional anesthesia (Group RA, n=18). The demographic characteristics, procedure, and hospital data were evaluated.Results: There were no significant differences betveen two groups with regards to gender, height, weight, body mass index, ASA scores, perioperative colloid and crystalloid fluid consumptions. Duration of anesthesia and procedure in Group RA was shorter than that in Group GA. The requirement for invasive arterial monitorization, central venous catheterisation, and nasogastric tube in Group GA was higher than that in Group RA. Postoperative delirium was similar in both groups. Heart rate, mean arterial pressure, and peripheral oxygen saturation were similar. In-hospitality mortality was 26.3% in the entire group of centenarians.Conclusions: This study examined the role of different anesthetic methods in extremely elderly patients over 100 years old during different surgeries. Anesthetic agent preferences, long duration of anesthesia and surgery, and hemodynamic instability can cause serious complications. We therefore conclude that careful considerations are required in extremely elderly patients.